Digital Literacy Campaign to Improve the Community's Economy - Lyandra Arianti (Jurnal PKM Manajemen Bisnis, 2023)
The growing digital era has had a significant impact on various aspects of life, including the economy. Digital understanding and proficiency is key to helping society deal with this change. Therefore, we held a community service program entitled "Digital Literacy Campaign to Improve the Community's Economy" to provide training and support to the community in increasing their understanding and application of digital technology in their businesses. The main objective of this activity is to increase people's ability to use digital tools to increase their economic potential. We aim to provide practical training on using digital technology, increase their access to digital resources, and help them grow their business online. This activity is carried out through a series of workshops, training, and consultation sessions involving participants from various backgrounds. Teaching methods focus on understanding the basics of digital technology, practical application in business, and using the internet for marketing and sales. We also provide access to digital resources and ongoing support. This activity succeeded in providing significant benefits to the community. Participants experience increased skills in managing their business digitally, from website creation to online marketing. Several participants reported a significant increase in their sales and income after applying the knowledge they had acquired. In addition, this activity also strengthens connections between members of the community and promotes collaboration in dealing with digital economy challenges.